INTEGRATING CHARACTER EDUCATION INTO ENGLISH LANGUAGE TEACHING MATERIALS: A STRUCTURED NARRATIVE REVIEW AND PEDAGOGICAL DESIGN SYNTHESIS - Fitriani Fitriani; Fitriah Hayati; Nurul Fatehah Binti Norhazaruddin (Sensei International Journal of Education and Linguistic, 2026)
Character education is very important in Indonesia because it is mandated in the curriculum, but in the English subject the teacher usually only teaches the language and the character is forgotten. Actually English materials can also contain character values if the material is designed well. This article discusses the integration of character education into English language teaching materials. The method used is literature review from many international journals and also books. The result shows that character education can be integrated into reading, writing, speaking, and listening if the material has clear values and the students are asked to reflect. But there are also challenges, for example the teacher is not ready and the value is only given like a lecture. Therefore the material developer must design the material carefully so that the value is not separated from the language.